PERANAN PEMERINTAH KABUPATEN BATU BARA DALAM PENGELOLAAN DAN PENDAYAGUNAAN SUMBER HUTAN BAKAU (STUDI DI DINAS LINGKUNGAN HIDUP KABUPATEN BATU BARA) - Nizar Putra Lubis; Irdiyansyah Sitorus; Mhd Ikhfan Safira; Fahrul Ilmi; Yanrus Sibuea; Prasetia Rambe; Erwin Syahputra (Nusantara Hasana Journal, 2022)
This legal research uses empirical legal research methods and conducts a study at the Environmental Service Office of Batubara Regency. In this legal research, primary legal materials are used, namely: Legislation. Secondary legal materials, namely: law books. Tertiary legal materials, namely: non-legal books. In this study, that the role of the Batu Bara Regency Government in the Management and Utilization of Mangrove Forest Resources is currently experiencing obstacles in following up on the logging of mangrove forests in the Batubara Regency area, then in law enforcement for these crimes in the forestry sector, in this case it has shown that the legal provisions in the forestry sector cannot be accommodated for the development of an existing crime. In dealing with crime cases in the forestry sector, which in this case have recently developed, are growing and also getting wider.